Time-history blast response and failure mechanism of RC columns using Lagrangian formulation. (December 2021) - Zhang, Chunwei; Abedini, Masoud
Abstract: Structural behavior of RC structures under explosive loads is an emerging field of research especially RC columns since the damage of RC columns can lead to progressive collapse. Most research works investigated and concentrated on the behavior of RC columns when exposed to far-field detonations (FFD). A limited study is available on the effects of near-field detonation (NFD) and close-in detonation (CID) on the behavior of RC columns. Hence, the main purpose of the current research is to investigate the influence of different types of detonation scenarios on the dynamic behavior of RC columns. The influences of extreme loading conditions on the columns are defined by using Lagrangian analyses in LS-DYNA. Validation of the numerical model is implemented by comparing the numerical analysis results with UFC 3–340-02 Standard. It is shown that the model yields a reliable prediction of damage on all RC columns. Intensive studies are performed to evaluate the influences of various scaled distances on the dynamic behavior of the columns. The results demonstrated that when the columns are subjected to CID explosions, they undergo the maximum pressure and the columns fail due to severe impulsive regime loading. The results revealed that when the scaled distance is in the CID range, the peak blast load increases but the duration of the positive phase of the blast wave decreases resulting in higher amplitude, lower-duration shock pulse and when the scaled distance is in the FFD range, the peak blast load decreases but the duration of the positive phase blast wave increases resulting in lower amplitude, longer-duration shock pulse. Also, the results show that increasing the scaled distance in RC columns subjected to NFD and FFD detonations resulted in a further decrease in the peak deflection histories and damage degree of RC columns in comparison to CID explosions. The current investigation and the outcomes can be utilized for evaluation of the effect of an explosion on the RC columns.